1973
DOI: 10.1677/joe.0.0570055
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Specificity in the Suppression of Sexual Receptivity of the Female Golden Hamster

Abstract: Oestrogen\p=m-\progesterone-induced lordosis behaviour was suppressed in female hamsters which received neonatal treatment with testosterone propionate or diethylstilboestrol. No suppression of lordosis was observed in females which received neonatal treatment with testosterone, androsterone or control substances. In addition, the ano\p=m-\genital distance and diameter of the vaginal orifice were increased in females treated with testosterone, testosterone propionate, androsterone or diethylstilboestrol.Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In addition, estradiol treatment following prepubertal OVX also defeminizes adult behavior, indicating that estradiol is the ovarian hormone driving behavioral defeminization during adolescence (Schulz & Sisk, 2006). While it may be surprising that ovarian hormones defeminize female lordosis behavior during adolescence, estrogen-receptor mediated behavioral defeminization also occurs during the perinatal period of development (Clemens & Gladue, 1978; Coniglio, Paup, & Clemens, 1973; Paup, Coniglio, & Clemens, 1972; for review see Wallen & Baum, 2002). Whether ovarian hormone-induced defeminization of lordosis behavior during adolescent development negatively impacts female reproductive success is not known.…”
Section: 4 Hormone-dependent Behavioral Organization During Pubertymentioning
confidence: 99%
“…In addition, estradiol treatment following prepubertal OVX also defeminizes adult behavior, indicating that estradiol is the ovarian hormone driving behavioral defeminization during adolescence (Schulz & Sisk, 2006). While it may be surprising that ovarian hormones defeminize female lordosis behavior during adolescence, estrogen-receptor mediated behavioral defeminization also occurs during the perinatal period of development (Clemens & Gladue, 1978; Coniglio, Paup, & Clemens, 1973; Paup, Coniglio, & Clemens, 1972; for review see Wallen & Baum, 2002). Whether ovarian hormone-induced defeminization of lordosis behavior during adolescent development negatively impacts female reproductive success is not known.…”
Section: 4 Hormone-dependent Behavioral Organization During Pubertymentioning
confidence: 99%
“…While it may seem counterintuitive that ovarian hormones defeminize female lordosis behavior during adolescence, estrogen-receptor mediated behavioral defeminization also occurs during the perinatal period sensitive period (Clemens and Gladue, 1978; Coniglio et al, 1973; Paup et al, 1972; for review see Wallen and Baum, 2002). Whether estradiol-induced defeminization of lordosis behavior during development negatively impacts female reproductive success is not known.…”
Section: Ovarian Hormone Exposure During Adolescence Organizes Femalementioning
confidence: 99%
“…Animals treated with norethindrone achieved a significantly higher frequency of mounting than the animals treated with progesterone (Duncan's <0·05). Scores for animals treated with dydrogesterone were not different from those for animals treated with progesterone and the latter were not 272 A. J. Vomachka et al different from controls injected neonatally with sesame oil (Coniglio et al, 1973).…”
Section: Male Behaviourmentioning
confidence: 73%
“…While the hamsters treated with progesterone and dydrogesterone exhibited fewer lordosis responses, their responses were of longer duration. Comparison of lordosis scores of these groups with females given oil injections neonatally and tested under similar conditions (Coniglio et al, 1973) revealed no significant difference between dydrogesterone and control animals. The lordosis duration of the progesterone group, however, was significantly shorter than that of the § io control animals (Duncan's, P<0-05).…”
Section: Female Behaviourmentioning
confidence: 89%
See 1 more Smart Citation